2009
DOI: 10.1186/1471-2296-10-37
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel intervention to promote colorectal cancer screening among community health center patients: results of a pilot study

Abstract: Background: Colorectal cancer screening rates are low among poor and disadvantaged patients. Patient navigation has been shown to increase breast and cervical cancer screening rates, but few studies have looked at the potential of patient navigation to increase colorectal cancer screening rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
125
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 24 publications
2
125
2
Order By: Relevance
“…Based on this definition, we describe our study as an implementation trial. Many prior trials to promote CRC screening have been conducted in clinical settings [10][11][12][13][14][15][16][17]. While a few pilot studies have demonstrated the feasibility of promoting CRC screening in community settings such as churches [18][19][20], few large trials have been conducted in these venues [21,22].…”
mentioning
confidence: 99%
“…Based on this definition, we describe our study as an implementation trial. Many prior trials to promote CRC screening have been conducted in clinical settings [10][11][12][13][14][15][16][17]. While a few pilot studies have demonstrated the feasibility of promoting CRC screening in community settings such as churches [18][19][20], few large trials have been conducted in these venues [21,22].…”
mentioning
confidence: 99%
“…Consistent with the literature on implementation, interventions that use a number of different strategies seem to be most effective, and almost all the studies reviewed for the present work used multiple intervention approaches. Some recommendations proposed for enhancing screening in low-income populations included the development of additional educational materials aimed at individuals with a low literacy level 13 ; the use of patient activation, including empowering patients to ask their health care providers about screening 41 ; and the promise of patient navigators 18,36 or lay health advisors 20 as approaches to reduce disparities.…”
Section: Evidence From Research Into Screening Promotion Interventionsmentioning
confidence: 99%
“…Panel management has been shown to improve health outcomes among patients with a range of conditions, including lowering glycosylated hemoglobin levels in patients with diabetes [6][7][8], and improving smoking cessation rates [9] and self-reported quit attempts by patients who use tobacco products [10]. Panel management has also been shown to enhance care processes, increasing the rates of vaccination and bone density screenings [11], as well as screenings for colorectal and breast cancer [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%